1966
DOI: 10.1149/1.2423780
|View full text |Cite
|
Sign up to set email alerts
|

Photocurrents Produced by Ultraviolet Irradiation of Mercury Electrodes

Abstract: The influence on the photocurrent of factors such as wavelength, scavenger concentration, ionic strength, diffusion coefficient of the hydrated electron, and the nature of products of the scavenging reaction, is considered. The discussion is illustrated by experimental data obtained by a variety of methods, and some preliminary results for substantially monochromatic light are described which lead to approximate relative rate constants for the scavenging of hydrated electrons by some simple inorganic ions and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
30
0
1

Year Published

1968
1968
2014
2014

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 153 publications
(32 citation statements)
references
References 10 publications
1
30
0
1
Order By: Relevance
“…The concept was postulated as early as 1965 by Barker et al who proved that at certain electrode potentials and photon energies the observed photocurrent arises from photoelectron emission from the metal into the electrolyte solution. 16 Prior to his work, Berg attributed experimentally observed photocurrent at a mercury electrode to the absorption of light by the metal and production of "hot electrons" causing an increase of the electron transfer rate to the solute in the solution. 17 Heyrovsky invoked the concept of photodecomposition of surface charge transfer complexes formed between a metal and a solvent or solute.…”
Section: Introductionmentioning
confidence: 99%
“…The concept was postulated as early as 1965 by Barker et al who proved that at certain electrode potentials and photon energies the observed photocurrent arises from photoelectron emission from the metal into the electrolyte solution. 16 Prior to his work, Berg attributed experimentally observed photocurrent at a mercury electrode to the absorption of light by the metal and production of "hot electrons" causing an increase of the electron transfer rate to the solute in the solution. 17 Heyrovsky invoked the concept of photodecomposition of surface charge transfer complexes formed between a metal and a solvent or solute.…”
Section: Introductionmentioning
confidence: 99%
“…At a given potential the photocurrent was proportional to the square root of the nitrate concentration (0.1-10 mm) in good accordance with Barker's theory. 1) According to the Barker model of the process, the photoelectrically emitted electrons are ther-(image force) is in balance with the thermal energy of the electron, i.e., (1) ( 2) where K1 and K2 are the constants.…”
mentioning
confidence: 99%
“…The last statement means, that in the region z < 0 the quantity lvfl remains approximately constant when Ef changes in the considered threshold energy interval AE. This constancy evidently takes place also at the point z = 0, and it follows then, that Iyi!z=o = const being approximately independent of p. The last equality is t o be used as an appropriate boundary condition for equation (3).…”
Section: General Expression For the Partial Current Densitymentioning
confidence: 93%